Analisis Prinsip 5C pada Pembiayaan Multiguna PT Bank Sumut KCP Syariah Multatuli - Laksmiarti, Diksi; Inayah, Nurul (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study analyzes how to apply thea5C principles (character,bCapacity,bCapital,bCollateral, Condition of Economy) in the provision of multipurpose financing at PT.bBank ofbNorth Sumatra KCP Syariah Multatuli. Thedresearch methodcused isba qualitative method with a descriptive approach. Sources of data consisting of primary data andcsecondary data. The technique of collectingddata through primary data is by interviewing by asking several questions related to the 5C principle to the informants of the Account Officer section of PT. Bank Sumut KCP Syariah Multatuli as well as collecting documentation data and browsing through the internet. The results show that the important points of the character principle are the personality of the customer, the principle of capacity isbthe size of the salary, capital is a salary that is sufficient for the ratio of financing, collateral isba guarantee, and the Condition of Economy is to assess the condition of the salary ratio of customers as employees, ASN or civil servants.